WHETHER THERE WILL BE AN EFFECT FROM EFFECTIVE CONTRACT IN THE SYSTEM OF HIGHER EDUCATION? - G. N. KRAYNOV (Высшее образование в России)
The article addresses the issues concerning the implementing of effective contract in higher education institutions. The author analyzes this problem through a prism of possible increase of labor productivity of university teaching staff and adduces criteria for the evaluation of the efficiency of peofessors’ work and for assigning the stimulating payments. The author points out that there is a devaluation of the initial sense and understanding of the term “effective contract” towards its use as an administrative “whip”. It is treated in terms of a new “managerialism” and considered as an instrument of Russian universities’ entry into global rankings. So, the professors are imposed to fulfill financial and commercial duties. Professor’s conversion into a business unit won’t become the effective mechanism of improvement Russian higher education. The trust labour relationships shouldn’t be replaced with market trust relationships. The author comes to a conclusion that the system of effective contract is still undeveloped and demands the further analysis both on institutional, and at the functional level.